A Study of Asphalt Mixes with Natural Fibre (Sisal Fiber) By Experiment (International Journal of Innovative Research in Computer Science & Technology, 2022)
The main aim of this study was to  determine the benefits of use of naturally available Fibre  called SISAL fibre used as additive in Bituminous concrete.  Bituminous Mixture In which all component were mixed,  placed and compacted at High temperature is called as Hot  Mix Asphalt. HMA grade is referred as Dense Grade  mixture (DGM). Asphaltic concrete is also called  Bituminous Concrete (BC). Pavements are vulnerable to  cracks, potholes, distresses and permanent deformation. In  this study, SISAL fiber used in bitumen mixtures to study  the benefits of using natural fibers, Eco-friendly design.  Standard Marshall mix design test and drain down test were  carried out. The process of mixing and preparing  aggregates,The grading was done according to the  specifications of (ISMORTH).Various percentages of  binder changed to (4.5% -5.5%) and the added fiber  changed to (0.1% -0.7%) of total aggregate and dust as a  filler. The optimal value for bitumen is determined using  the Marshall method and was found (5%). Similarly, the  optimum fiber content of bitumen concrete (BC) was found  (0.3%). Samples of Bituminous concrete (BC) mix were  made and run those for obcs and of cs, then run them in tests  such as Marshall Stability and Drain Down test to evaluate  the result of adding fiber to the bitumen mixture. The test  results indicates that the modification of bitumen with sisal  fiber is used as an additive for bitumen mix, the Blends help  increase stability and durability, reduce air void and flow  value. After all, it was found that the use of Sisal fiber as an  additive improves the properties. Like Stability, strength,  durability, reduce drain down of bituminous concrete (B.C).
Keywords: Asphalt mix; Sisal Fibre; Bituminous Concrete; Dense Grade mixture; Aggregates